Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to compute the following limit?

$\lim\limits_{n\to\infty} n·(\sqrt[n]{a}-1)$

We know that it's got something to do with $\ln$ or $\exp$.

We know that $\lim\limits_{n\to\infty} \sqrt[n]{a} = 1$ but it seems to not to be true that therefore $\lim\limits_{n\to\infty} n·(\sqrt[n]{a}-1) = \lim\limits_{n\to\infty} n·(1-1) = 0$.

What we know is

$\lim\limits_{n\to\infty} (1-\frac{1}{n})^n = \lim\limits_{n\to\infty} (1 + \frac{1}{n})^n \lim\limits_{n\to\infty} (1-\frac{1}{n})^{n+1} = e$

and

$\lim\limits_{n\to\infty} (1+\frac{x}{n})^n = \exp(x)$

share|improve this question
4  
Hint: You can use the fact that $\lim\limits_{x\to0} \frac{a^x-1}x$ is precisely the derivative of the function $f(x)=a(x)$. (In case you've already learned about derivatives and are allowed to use them.) –  Martin Sleziak Mar 26 '12 at 14:27

4 Answers 4

up vote 4 down vote accepted

Substitute $t=\frac{1}{n}$ , hence :

$L=\displaystyle \lim_{t \to 0} \frac{a^t-1}{t}$

Now , apply L'Hopital rule ,hence :

$L=\displaystyle \lim_{t \to 0} a^t \cdot \ln a=\ln a$

share|improve this answer
1  
Actually $L$ is the definition of the derivative of $a^{t}$ at 0. You should get it from the definition, since applying L'H in this case would be circular logic.... –  N. S. Mar 26 '12 at 15:03
1  
@N.S. This was one tricky thing I learned in my first year of university. Applying l'Hospital to basic limits is circular logic because you literally use the value of the limit when proving the formula for the derivative. –  Beni Bogosel Mar 26 '12 at 15:16

Here's how Wolfram|Alpha solves it.

share|improve this answer
    
the edit broke the link. –  Tyler Mar 26 '12 at 15:10

Using Taylor's expansion, $$ n(\sqrt[n]{a}-1)=n(e^{\frac1n\log a}-1)=n(1+\frac1n\,\log a+o(\frac1{n^2})-1)=\log a + o(\frac1n)\xrightarrow{n\to\infty}\log a. $$

share|improve this answer

Set $x_n=n(\sqrt[n]{a}-1)$ for all $n$. Rearranging this you get $(\frac{x_n}{n}+1)^n=a$ for all $n \in \mathbb{N}$. But this also means that $$(\frac{x_n}{n}+1)^n \rightarrow a=e^{\ln(a)}$$ as $n\rightarrow \infty$. Hence we must have $x_n \rightarrow \ln(a)$ as $n \rightarrow \infty$.

share|improve this answer
1  
Nice solution. The last part, namely that $x_n \to \ln(a)$ needs a little justification though.. It follows easely if you observe that $\ln(a)$ is the only limit point of $x_n$. –  N. S. Mar 26 '12 at 15:05
    
Thanks :) I left it out intentionally. I think it can be instructive for the OP the fill in the details. But never the less you are of course correct. Formally, if $x_n$ do not converge to $ln(a)$, then since the sequence of $x_n$:s obviously is bounded, we could find a subsequence converging to a number c not equal to ln(a), which is a contradiction –  user22705 Mar 26 '12 at 16:01

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.